Determinant of the share prices of the food and beverages company listed in Bursa Malaysia / Nur Atiqah Zaraan and Nur Amirah Abdul Rahim - Zaraan, Nur Atiqah; Abdul Rahim, Nur Amirah (Faculty of Business and Management, 2016)
First and foremost, we would like to express thank to Allah SWT for blessing us with all the required knowledge, health and courage to completing this research project. We also have to express our appreciation toward our first advisor, Madam Khaizie Sazimah Ahmad and Madam Jumaelya Jogeran as second advisor. Without her guidance and knowledge that she gives to us in every step throughout the process, this research would not be complete within the duration. We would like to express a lot of thank you for all your support and understanding during us doing this research. Most importantly, without fully support from our family, we could not complete this project paper. With them we can complete our research as well as degree study.